Measurement of an enlarged blood pump model - Leo, Hua Liang. (2008)
Centrifugal pumps have been used as a form of circulatory assist device for more than a decade now. However they are still plagued by hemolysis and the formation of thrombi, and these have greatly limited their life as a replacement of our vulnerable heart. With the advent of the magnetically suspended blood pump in artificial heart research, the index of hemolysis has greatly been reduced. However, there is still lack of measurements on the flow profile within the pump due to its small size. Hence a five times scaled up model of the Bio-Centrifugal pump was developed, using Laser Doppler Anemometer (LDA) to measure the flow field in between the blade passages of three different impellers configuration.